ANALISIS RESPONS ARUS D–Q UNTUK EVALUASI STABILITAS TRANSIEN GENERATOR SELAMA GANGGUAN JARINGAN - Noor, Nurul Chairunnisa (Yayasan Nusantara Hasana Berdikari, 2025)
The integration of wind power plants into Indonesia’s electrical grid requires a high level of operational reliability, particularly during network disturbances that trigger temporary voltage dips. Low Voltage Ride Through (LVRT) conditions pose a major challenge, as they can induce transient instability in the generator and potentially lead to turbine disconnection from the grid. This study aims to evaluate the transient stability of a wind turbine generator during grid disturbances by analyzing the current response in the d and q axes, which serves as a key dynamic indicator within the wind energy conversion system. To enhance the turbine's ability to remain connected during LVRT events, a STATCOM controlled by a Linear Quadratic Regulator (LQR) is employed to provide rapid and adaptive reactive power compensation. Simulations are conducted to observe the oscillation patterns, damping behavior, and steady-state conditions of both current components following the disturbance. The results demonstrate that the d–q axis currents exhibit well-damped oscillations, return smoothly to steady-state values, and show no signs of divergence. These findings confirm that the LQR-controlled STATCOM significantly improves transient stability, enhances the operational reliability of wind power plants, and supports the safer and more sustainable integration of renewable energy into the electrical grid.